Insurance requirements of the Greek mariculture industry during the period 1986-1994 (1st semester) - Christofilogiannis P.; Theodorou J. (Aspects économiques de la production aquacole, 1995)
The Insurance requirements of the Greek Mariculture Industry have been collected and analysed in terms of causes and money value. Special attention has been paid to the evolution of each factor in relation to time. The causes of damages become more specific in the early 90's due to the increase of knowledge and experience of the cultured species. The present effort has shown that insurance records could be used as a useful tool in order to evaluate the status of the industry.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/05/17-19, Montpellier (France)